Rekonstruksi Bahan Ajar Mahārah Al-Kalām Berbasis Tsaqāfah Pesantren: Studi Research and Development di Ma’had Ar-Rosyad Kediri - Dagi Mardhan Agae Agni; M. Baihaqi (Program Studi Pendidikan Bahasa Arab of STAI Ali bin Abi Thalib Surabaya, 2026)
This study aims to reconstruct Arabic speaking skill (mahārah al-kalām) teaching materials based on pesantren culture (tsaqāfah pesantren) and examine their effectiveness in improving students’ communicative competence. The study is motivated by the dominance of structural and less contextual Arabic teaching materials that limit students’ opportunities to practice authentic communication. Previous studies have mainly focused on technological innovation and communicative approaches, while the integration of local sociocultural contexts into Arabic teaching materials remains limited. This research therefore proposes a contextual reconstruction of teaching materials by integrating authentic pesantren life into Arabic speaking instruction. This study employed a Research and Development (R&D) approach based on the Borg and Gall model, limited to the preliminary field testing stage. The research was conducted at Ma’had Ar-Rosyad Kediri involving 8 intermediate-level students selected purposively. Data were collected through observation, interviews, expert validation questionnaires, student response questionnaires, and speaking tests using pre-test and post-test designs. Data analysis used paired sample t-test and thematic qualitative analysis. The findings reveal that the developed materials are pedagogically feasible and effective in improving students’ speaking ability. The average score increased from 64.37 in the pre-test to 76.7 in the post-test, while the t-count value (3.58) exceeded the t-table value (2.36) at the 5% significance level. The novelty of this study lies in reconstructing mahārah al-kalām materials by positioning tsaqāfah pesantren as an authentic communicative environment within Arabic language learning.